Q-switched and dark pulse harmonic mode-locked all-fiber lasers using interference filters / Chi Mingzhi - Chi , Mingzhi (2025)
Interference filters, pivotal optical devices harnessing the principle of interference to selectively transmit or reflect specific wavelengths of light, stand as indispensable tools across diverse domains such as communication, sensing, medical, industrial, and scientific fields. This dissertation embarks on exploring the efficacy of multimode or cladding mode interference in pulse generation. Initially, it proposes and demonstrates a passively Q-switched all-fiber laser, leveraging a multimode double-clad Erbium-Ytterbium co-doped fiber as an active medium. The Q-switching mechanism, facilitated by the Kerr effect of multimode interference, induces intensity modulation within the linear cavity laser. Stable Q-switched pulses at 1552.3 nm are achieved, with a repetition rate ranging from 50.3 to 222.2 kHz and shortest pulse width of 2.1 μs, alongside a peak pulse energy of 2.7 μJ at a pump power of 2.42 W. This unveils a novel modulation mechanism for obtaining high-energy pulses within an all-fiber linear cavity. Subsequently, the study demonstrates the realization of harmonic domain-wall dark pulses in a C-band fiber laser. The self-started domain-wall dark pulse at a mere pump power of 112 mW exhibits a fundamental repetition rate of 0.96 MHz, pulse width of 250 ns, and a maximum average pulse energy of 3.24 nJ. Furthermore, the experiment reveals the visualization and quantification of dark pulses up to the 7th harmonic order, with a minimum pulse width of 60 ns recorded in the 7th order. Remarkably, the harmonic dark pulse fiber laser exhibits commendable stability, maintaining signal-to-noise ratios above 50 dB across all harmonic operations. The pursuit of harmonic dark pulse dark soliton presents a promising pathway for fostering sustainable industrial advancement in the future.